2018
DOI: 10.1002/jemt.23031
|View full text |Cite
|
Sign up to set email alerts
|

Calcifications in prostate cancer: An active phenomenon mediated by epithelial cells with osteoblast‐phenotype

Abstract: The main aim of this study was to investigate putative correlation between the formation of prostate calcifications and the presence of cancer cells showing the ultrastructural and morphological aspects of osteoblasts. To this end, 40 prostate biopsies of prostate cancer were enrolled and investigated from histological, immunohistochemical, and ultrastructural point of view. To the best of our knowledge, this is the first study to propose a new cell type related to the ectopic calcifications in prostate tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 10 publications
4
28
0
Order By: Relevance
“…Immunohistochemical analysis of vimentin expression was performed in order to evaluate the number of prostate cells that acquire mesenchymal phenotype (Figure 1(a)–1(c)). As shown in a recent study [24], significant group effect was detected in the rate of vimentin-positive prostate cells ( p =0.0025), and post hoc testing showed a significantly higher rate of vimentin-positive prostate cells in BM+ (274.4 ± 30.76) compared to both BL (90.79 ± 14.82) and BM− (198.8 ± 22.8) (BL vs BM− p =0.0298; BL vs BM+ p < 0.0001; BM− vs BM+ p =0.047).…”
Section: Resultssupporting
confidence: 56%
“…Immunohistochemical analysis of vimentin expression was performed in order to evaluate the number of prostate cells that acquire mesenchymal phenotype (Figure 1(a)–1(c)). As shown in a recent study [24], significant group effect was detected in the rate of vimentin-positive prostate cells ( p =0.0025), and post hoc testing showed a significantly higher rate of vimentin-positive prostate cells in BM+ (274.4 ± 30.76) compared to both BL (90.79 ± 14.82) and BM− (198.8 ± 22.8) (BL vs BM− p =0.0298; BL vs BM+ p < 0.0001; BM− vs BM+ p =0.047).…”
Section: Resultssupporting
confidence: 56%
“…In light of this, it is possible to speculate an increase of the uptake of sestamibi in breast cancers with a high number of BOLCs due to the increase of the high-transmembrane-potential mitochondria during the formation of microcalcifications made of HA that are generally produced by the BOLCs themselves. In agreement with this evidence, ultrastructural observations demonstrated the presence of several mitochondria, both in osteoblast-like cells and real osteoblasts during calcification production [10,23,24]. Therefore, BSGI with [ 99 mTc]Tc-Sestamibi could be used to stratify breast cancer patients based on the risk of developing bone metastases given the presence of a high number of BOLCs.…”
Section: Discussionsupporting
confidence: 65%
“…Interestingly, Energy Dispersive X-Ray (EDX) -microanalysis revealed that Mg-HAp calcifications appeared in conjunction with malignant lesions exclusively [7]. Recent discoveries in the field of the biology of breast and prostate calcifications demonstrated the presence of cells capable to produce calcified crystals [7,9]. In addition, our and other studies showed that only the complex form of calcification (HA and Mg-HAp) were produced by these cells (osteoblast-like cells) [7].…”
Section: Introductionmentioning
confidence: 65%